2012
DOI: 10.1071/wr11167
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for source - sink dynamics in a regional population of arctic ground squirrels (Urocitellus parryii plesius)

Abstract: Context Variable demographic rates can manifest themselves between habitat types in the form of source–sink dynamics where populations in sink habitats would not exist without the addition of migrants from source habitats. Aims Arctic ground squirrels (Urocitellus parryii pleisus (Osgood, 1900)) occupy a large geographic area in northern Canada and live in a variety of habitat types, including boreal forest, low-elevation meadows and alpine meadows, providing an opportunity to investigate the possible existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Other studies provide evidence that biotic factors alone can form lower limits. For example, shrub habitats were considered population sinks for Arctic ground squirrels Urocitellus parryii due to high predation rates (Donker & Krebs, ). This dynamic was also confirmed for arctic hares Lepus arcticus through a series of experiments (Barta et al, ; Small & Keith, ).…”
Section: Review Of Evidence For Irltmentioning
confidence: 99%
“…Other studies provide evidence that biotic factors alone can form lower limits. For example, shrub habitats were considered population sinks for Arctic ground squirrels Urocitellus parryii due to high predation rates (Donker & Krebs, ). This dynamic was also confirmed for arctic hares Lepus arcticus through a series of experiments (Barta et al, ; Small & Keith, ).…”
Section: Review Of Evidence For Irltmentioning
confidence: 99%
“…For example, female Columbian ground squirrels (Spermophilus columbianus (Ord, 1815) = Urocitellus columbianus (Ord, 1815)) that are lighter during spring will often not reproduce, but experience greater subsequent overwinter survival compared with heavier females that successfully raise litters (Neuhaus 2000). Similarly, Donker and Krebs (2012) found that AGS overwinter survival was higher, but reproduction was lower, in the boreal forest habitat than in the low meadow habitat.…”
Section: Body Massmentioning
confidence: 89%
“…Such systems, defined as 'duck holes', may represent more transient colonies in marginal habitat or burrowing activity associated with territorial disputes or interactions with predators (Carl 1971). The potential for source-sink dynamics has been suggested for arctic ground squirrels (Gillis et al 2005a;Donker and Krebs 2012). Burrowing activity with such characteristics may be indicative of sink-like populations or transient habitat associations.…”
Section: Discussionmentioning
confidence: 99%
“…Indications of source-sink dynamics have been identified in arctic ground squirrels (Donker and Krebs 2012) and allow this species to occur in marginal habitat. Habitats of marginal quality may become less frequently occupied if high-quality (presumably forb-rich and lacking in dense high-stature vegetation) habitat becomes rarer.…”
Section: Discussionmentioning
confidence: 99%